2006
DOI: 10.1007/s00192-006-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of voiding difficulty after TVT, its impact on quality of life, and related risk factors

Abstract: Symptoms of VD occurred after TVT and caused lesser improvement in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Another study is ongoing to evaluate multichannel urodynamics and uroflowmetry in different positions in all the patients. Using urodynamic evaluation to identify functional obstruction after TVT has been done in several studies [27][28][29][30][31] in which an increase in maximum urethral closure pressure, decreased peak and mean flow rates, and increased voiding detrusor, mean detrusor pressure, and mean urethral resistance have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another study is ongoing to evaluate multichannel urodynamics and uroflowmetry in different positions in all the patients. Using urodynamic evaluation to identify functional obstruction after TVT has been done in several studies [27][28][29][30][31] in which an increase in maximum urethral closure pressure, decreased peak and mean flow rates, and increased voiding detrusor, mean detrusor pressure, and mean urethral resistance have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, patients undergoing prolapse repair and concomitant antiincontinence surgery were more likely to have elevated PVRV after surgery than those receiving prolapse repairs alone. Vervest et al [26] reported that women with preoperative voiding difficulty who undergo TVT combined with prolapse surgery are at significant risk for developing urinary retention. In contrast, Sokol et al [27] reported that the risk of developing postsurgical urinary retention was statistically similar between TVT procedures with and those without prolapse repair.…”
Section: Discussionmentioning
confidence: 99%
“…Voiding dysfunction, defined as obstructive voiding symptoms, irritative voiding symptoms, urinary retention, urgency, or urge incontinence, has been reported in as many as 60% of patients who have had anti-incontinence surgery [10]. In one group's review of the literature, voiding dysfunction occurred in 5% to 7% after needle suspension, 2% to 4% after TVT, 5% to 20% after a Marshall-Marchetti-Krantz procedure, and 4% to 22% after Burch colposuspension [11].…”
Section: Postoperative Voiding Dysfunctionmentioning
confidence: 97%